Effect of a meal feeding schedule on hepatic glycogen synthesis and gluconeogenesis in rats - Batista, M. R.; Curi, R.; Lima, F. B.; Lopes, G.; Bazotte, R. B. (My University, 2001)
We investigated the effect of a meal feeding schedule (MFS) on food intake, hepatic glycogen synthesis, hepatic capacity to produce glucose and glycemia in rats. The MFS comprised free access to food for a 2-hour period daily at a fixed mealtime (8.00-10.00 a.m.) for 13 days. The control group was composed of rats with free access to food from day 1 to 12, which were then starved for 22 h, refed with a single meal at 8.00-10.00 a.m. and starved again for another 22 h. All experiments were performed at the meal time (i.e. 8.00 a.m.). The MFS group exhibited increased food intake and higher glycogen synthase activity. Since gluconeogenesis from L-glutamine or L-alanine was not affected by MFS, we conclude that the increased food intake and higher glycogen synthase activity contributed to the better glucose maintenance showed by MFS rats at the fixed meal time. Copyright © 2001 National Science Council, ROC and S. Karger AG, Basel.
Keywords: Feeding behavior; Glycemia; Glycogen synthase; Hepatic gluconeogenesis; Liver metabolism; Meal feeding; Metabolic adaptations; Ureagenesis; glycogen; glycogen synthase; animal experiment; controlled study; enzyme activity; feeding behavior; food intake; gluconeogenesis; glucose blood level; glycogen liver level; glycogen synthesis; liver metabolism; male; nonhuman; priority journal; rat; urea cycle; Alanine; Animals; Blood Glucose; Feeding Behavior; Food Deprivation; Gluconeogenesis; Glucose; Glutamine; Glycogen Synthase; Lactic Acid; Liver; Liver Glycogen; Male; Rats; Rats, Wistar; Time Factors; Urea